BIMBINGAN TEKNIS PENGELOLAAN PERPUSTAKAAN DAN PENGADAAN MEJA LIPAT DI MADINAH MAARIF 10 MALANG - Winda Harsanti; Suselo Utoyo; Agus Suhardono; Utami Retno P.; Mona Shinta S. (UPT Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Malang, 2020)
Madinah Maarif 10 is one of the nonformal education that operates in the religious field in Malang. In effort to maintain the quality of education and the quantity of students, Madinah established a library and once every year learning activities are held outside the Madinah. Library management is done by Madinah manager helped by students as assistants and supervised by head master of Madinah. To support activites which is done in outside Madinah, it is needed to make small folding table from wood so that light and stay longer.